2006
DOI: 10.1016/s0022-5347(18)32518-7
|View full text |Cite
|
Sign up to set email alerts
|

251: Transcriptomes of Human Prostate Cells

Abstract: Background: The gene expression profiles of most human tissues have been studied by determining the transcriptome of whole tissue homogenates. Due to the solid composition of tissues it is difficult to study the transcriptomes of individual cell types that compose a tissue. To overcome the problem of heterogeneity we have developed a method to isolate individual cell types from whole tissue that are a source of RNA suitable for transcriptome profiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…We named these genes 'Differentiation-Associated Hypermethylated' (DAH). Expression analysis of DAH genes in the same data sets 35,36 revealed that they are strongly enriched for genes downregulated in CaP tissues, and also in normal luminal cells (Figures 3b and c), supporting the hypothesis that these genes are, like GSTP1, mainly downregulated during differentiation and subsequently hypermethylated in CaP.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…We named these genes 'Differentiation-Associated Hypermethylated' (DAH). Expression analysis of DAH genes in the same data sets 35,36 revealed that they are strongly enriched for genes downregulated in CaP tissues, and also in normal luminal cells (Figures 3b and c), supporting the hypothesis that these genes are, like GSTP1, mainly downregulated during differentiation and subsequently hypermethylated in CaP.…”
Section: Resultssupporting
confidence: 66%
“…genes hypermethylated in CaP. We generated a comprehensive list of promoters hypermethylated in CaP from publicly available resources and assessed gene expression in three data sets: CaP versus normal prostate tissues, 35 luminal versus basal primary prostate cells, 36 CaP versus BPHderived basal cells. 29 As expected, 'genes hypermethylated in We then generated a list of genes highly expressed in prostate basal cells from BPH and CaP 29 and intersected it with the list of genes hypermethylated in CaP, finding 206 genes that are potentially regulated similarly to GSTP1 (Figure 3a and Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Another report using the same antiserum also showed a similar immunohistochemical staining pattern (27). To identify which populations of prostatic cells expressed AKR1C1 and AKR1C2, transcriptome analysis of four highly enriched populations of luminal, basal, stromal, and endothelial cells from the prostate was queried using the SCGAP Urologic Epithelial Stem Cells Project web site 5 (28). Relative expression profile from the most abundant to least revealed the following expression patterns: AKR1C1, stromal, luminal > endothelial >> basal; AKR1C2, stromal, luminal > endothelial > basal; and AKR1C3, basal, endothelial > stromal > luminal cells.…”
Section: Resultsmentioning
confidence: 99%
“…This qualifies antibacterial peptides such as defensins as candidates for an important role also in cancer development and manifestation. Thereby defensins may be expressed in prostate tissue [36] and/or immunocompetent cells [7] attracted to the sites of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%